A Human Being and the Ecology of Digital Media: The Implication of Social Media on the Thought and Expression of a Human Being (The International Journal of Educational Sciences and Arts, 2024)
This paper seeks, using the interpretive philosophical approach, to look into the issue of the impact of digital media on human life and ways of thinking and expression. This paper aims to analyze this issue interpretatively and link it to historical transformations in the field of media ecology in order to adopt a forward-looking view instead of a numerical analysis of the available information. The issue, as this paper sees it, lacks the philosophical dimension to discuss the characteristics of social media and link changes that these social media have brought on humans with changes that humans have brought on various concepts such as culture, thought, and society. This paper concluded that social media are a different revolution in communication media. It changed the procedures of the communication process, bringing the margin groups into the position of the elites and returning the elites to a position that is close to the position of the margin groups. The margins have become the agent that determines the ways of building new social relationships and carries out the process of transforming from traditional relationships to digital relationships. Thus, concepts change and are shaped by a different perception (the margin group). By carefully reading the characteristics of three social media (Twitter, Facebook, and WhatsApp), three common characteristics and features emerged that shaped and influenced their users: openness, permanence and continuity, and changing concepts.
Keywords: Media Ecology; Digital Media; Social Media